Character Narratives in Indonesian Digital Fiction: A Semi-Digital Stylistics Approach - Simanjuntak, Nensy Megawati; Padmasari, Arumtyas Puspitaning; Setyawan, Dedy; Tobing, Victor MTL; Prather, Sarah (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2024)
Digital fiction is a collection of art texts in the form of short stories and novels that combine technology, virtual space, media elements, and provide access to readers or netizens to carry out certain activities in it. Narratology of Characterization is the initial foundation in research in the field of literary studies. Narratology is a field of study that explains narratives and narrative structures in a discourse context. Narratology of characterization talks about the position or scheme of characters in the story. The position of the character talks about the role and impact of the role of the character. The character gives birth to characterization. Characterization gives birth to implications. Implications provides birth to messages and perspectives that will be captured by the reader. Narratology research in digital fiction is research that aims to explain the position, role, and function of the character and characterization itself. This study found that in digital fiction, characters are dominated by women. Female characters in digital fiction hold various roles and impacts on the roles they play. Not only that, this study also found that all works included in the digital fiction category are works that are ready to be owned by many people. Digital fiction does not only belong to the author but also to the reader who acts as a ghost writer who has the right to make decisions or provide suggestions and criticisms of the contents of the story. The author is still recognized as the creator of the story and netizens still take their position as figures who assess the work subjectively and objectively, subjective because there are thoughts, ideas, personal points of view in assessing a fiction, objective in providing assessments, input, suggestions, and criticisms for the maturity or goodness of the story.